Analysis of YouTube Videos as Educational Media Using the Naive Bayes Method - Phung, Mulan; Anggreiny, Phoebe Cecilia; Husada, Yusianne Kasih; Pangandaheng, Grasella Aldonia; Arwi, Adelia Vannissa; Mawardi, Viny Christanti (Journal of Computer and Information Systems Ampera, 2024)
Social media has become a way for people to socialize without meeting face to face, seek knowledge, sell, and so on. Analysis of the video “How Old is the Universe? (And How Do You Know?" aims to find out the public's response to educational videos on YouTube social media. With this research, it is hoped that social media can develop as an educational medium. First, 611 video comments were collected but only 100 comments could be analyzed. Then Pre-processing was carried out with the following steps: parsing, tokenization, stopword removal, and stemming. After that, comments were divided into 4 clusters based on the occurrence of the same words and their synonyms. Comments were also classified using 3 scales, namely negative, neutral, and positive. The initial 50 comments were manually classified while the other 50 comments used Rapidminer with the Naive Bayes method. Analysis of similar videos as comparative data also used the same steps. The results of the analysis showed a positive response of 65% with advantages in the use of animation and accurate scientific presentation. Based on the analysis, it can be concluded that YouTube is effectively used as an educational medium.